Penerapan Konsep Halal dalam Industri Farmasi dan Kosmetik di Indonesia: Tinjauan Bahan, Proses Produksi, Sertifikasi dan Tren Kosmetik Halal - Noviani Noviani; Muhammad Azhar Abdul Karim; Lisnawati Lisnawati (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to examine the implementation of halal principles in the pharmaceutical and cosmetic industries in Indonesia by reviewing aspects of raw materials, production processes, halal certification, and trends in the development of halal cosmetics. The method used is a literature study by analyzing various sources such as scientific journals, books, and regulations related to halal product assurance in Indonesia. The results show that the implementation of halal principles does not only focus on the permissibility of raw materials but also includes hygienic production processes that are free from contamination by non-halal substances. In addition, halal certification issued by authorized institutions such as the Halal Product Assurance Organizing Agency (BPJPH), supported by fatwas from the Indonesian Ulema Council (MUI), plays an important role in ensuring consumer trust. The implementation of halal principles in Indonesia is also strengthened by government regulations through Law Number 33 of 2014 concerning Halal Product Assurance, which mandates halal certification for products circulating in the market. On the other hand, the trend of halal cosmetics in Indonesia shows a significant increase in line with the growing public awareness of safe, halal, and high-quality products. Therefore, the implementation of halal principles in the pharmaceutical and cosmetic industries is not only a regulatory obligation but also a strategic opportunity to enhance industry competitiveness in both national and global markets.